Razzisti per natura, antirazzisti per cultura. Note critiche per un’antropologia pubblica e antirazzista - Bachis, Francesco (Antropologia Pubblica, 2024)
In the last decades, the anthropological debate about new racism and cultural fundamentalism reshaped the reflection on discrimination practices and hate speech. However, anthropology seems to have difficulty considering racism and anti-racism as research objects and thus fails to claim its role as a public and anti-racist discipline. Based on the use of digital ethnography as a form of redefinition of ethnographic practice, this article aims to reflect on the implicit and explicit forms of naturalization of the otherness in online hate speech and in antiracist discourses. In doing so, I will examine two “failures” of antiracist practices. 1) a live streaming on Facebook by the Italian newspaper La Repubblica that in the summer of 2017 followed a demonstration for the right to housing that take place after the eviction of asylum seekers and refugees from via Curtatone in Rome; 2) A public debate to which I took part together with a journalist and a migrant from Senegal on July of the same year in Sardinia (Italy). The article aims to reflect on the limits of public anthropology as an antiracist practice and on its ability to contrast hate speeches and new forms of racialization. Finally, the paper suggests that assuming the racist and antiracist common sense from a Gramsci’ perspective as a field of investigation and intervention of anthropology can offer a more effective position for a public and antiracist anthropology.